International Symposium on Code Generation and Optimization (CGO'07) 2007
DOI: 10.1109/cgo.2007.15
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Clustered VLIW Microarchitectures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…has a great impact on the quality of scheduling (2.). We observed that the estimation of the scheduling outcome without performing the actual scheduling, as done in [2], can be inaccurate. Nevertheless, it is a critical compilation decision since selecting a non-optimal frequency set can lead to a schedule with poor performance, energy consumption or both.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…has a great impact on the quality of scheduling (2.). We observed that the estimation of the scheduling outcome without performing the actual scheduling, as done in [2], can be inaccurate. Nevertheless, it is a critical compilation decision since selecting a non-optimal frequency set can lead to a schedule with poor performance, energy consumption or both.…”
Section: Introductionmentioning
confidence: 92%
“…The second step performs scheduling on the architecture configuration selected by step 1. This includes both cluster assignment and instruction scheduling, which in an unmodified [2] are in two separate steps.…”
Section: Phase Orderingmentioning
confidence: 99%
See 2 more Smart Citations
“…Clustered architectures [2,3,4,5] have been proposed to improve the scalability and performance by partitioning resources in critical timing paths like register files among clusters. However, the scalability achieved this way is still limited by traditional instruction encoding and centralized instruction execution control.…”
Section: Introductionmentioning
confidence: 99%